2020
DOI: 10.1038/s41598-020-60815-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial investigating Self-Assembling Peptide P11-4 for Treatment of Early Occlusal Caries

Abstract: Non-invasive caries treatment is a major focus in modern dentistry. The present study was designed to evaluate the effectiveness of monomeric self-assembling peptide P 11-4 (SAP P 11-4) in combination with fluoride varnish or polymeric self-assembling peptide matrix (SAPM) in treatment of non-cavitated occlusal caries. Ninety children and adolescents were included in this randomized, gold-standardcontrolled clinical trial. Test Group 1 received SAP P 11-4 and twice fluoride varnish at baseline and Day 180, Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…The combination treatment inactivated 80-100% of the carious lesions and caused regression into a lower ICDAS-II class in up to 30% of cases. In contrast, in the control groups solely receiving fluoride varnish, only 35% of the carious lesions were inactivated, and 6% regressed to smaller ICDAS-II class 17 and 20% needed restorative treatment during the 12 months study period 18 .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The combination treatment inactivated 80-100% of the carious lesions and caused regression into a lower ICDAS-II class in up to 30% of cases. In contrast, in the control groups solely receiving fluoride varnish, only 35% of the carious lesions were inactivated, and 6% regressed to smaller ICDAS-II class 17 and 20% needed restorative treatment during the 12 months study period 18 .…”
mentioning
confidence: 88%
“…Another early clinical trial has shown that, when SAP P 11 -4 is applied on proximal carious surfaces, it leads to an arrest or even regression of caries in 85% of cases as judged by standardized clinical radiographs 16 . Recent randomized gold-standard controlled clinical trials have shown SAP P 11 -4 combined with fluoride varnish or a Self-Assembling Peptide Matrix Gel to be superior for the treatment of early occlusal caries compared to fluoride varnish alone 17,18 . The combination treatment inactivated 80-100% of the carious lesions and caused regression into a lower ICDAS-II class in up to 30% of cases.…”
mentioning
confidence: 99%
“…The authors concluded that treatment of initial carious lesions with P 11 -4 led to better remineralisation of the subsurface lesions compared with the control teeth. Doberdoli et al 15 investigated the effectiveness of both monomeric self-assembling peptide P 11 -4 and the polymeric self-assembling peptide matrix in treatment of non-cavitated occlusal caries in children. The study showed that P 11 -4, applied either in combination with fluoride varnish or twice weekly as a gel was a superior treatment for early caries lesions, when compared to application of fluoride varnish alone.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biomimetic remineralisation strategies such as self-assembling peptides are considered to be a new perspective in caries prevention 13 15 . It is reported that the self-assembling peptide P 11 -4 forms a three dimensional matrix within the subsurface body of an initial enamel lesion and mimics enamel matrix proteins 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…P11-4 has since then been developed into a novel peptide based therapeutic for dental caries by inducing mineralisation. It was patented and marketed as Curodont TM Repair and is now widely available for the treatment of dental caries [ 72 ].…”
Section: Successful Peptide Based Therapeuticsmentioning
confidence: 99%